2013
DOI: 10.1155/2013/747240
|View full text |Cite
|
Sign up to set email alerts
|

Perimenopause Amelioration of a TCM Recipe Composed of Radix Astragali, Radix Angelicae Sinensis, and Folium Epimedii: AnIn VivoStudy on Natural Aging Rat Model

Abstract: Traditional Chinese medicine (TCM) has been extensively applied as preferable herbal remedy for menopausal symptoms. In the present work, the potential of a TCM recipe named RRF, composed of Radix Astragali, Radix Angelicae Sinensis, and Folium Epimedii, was investigated on a natural aging rat model. After administration of RRF (141, 282, and 564 mg/kg/d), the circulated estradiol (E2) level increased accompanied by a reduction of serum follicle stimulating hormone (FSH). But no significant impact on serum lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…It might be inferred that RRF exhibit estrogenic properties, and appeared to retard certain age-associated degenerations, shifting the endocrine dynamic towards a more physiologically favorable balance. The finding was in concert with our previous investigation on the ovariectomy middle-aged female rats as well as natural aging female rat model (Xie et al, 2013;Su et al, 2013). Hence, RRF may be endowed with potential beneficial effects in relieving perimenopausal symptoms, ameliorating deleterious degeneration in aspects of perimenopausal-associated pituitary-ovarian hormones.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It might be inferred that RRF exhibit estrogenic properties, and appeared to retard certain age-associated degenerations, shifting the endocrine dynamic towards a more physiologically favorable balance. The finding was in concert with our previous investigation on the ovariectomy middle-aged female rats as well as natural aging female rat model (Xie et al, 2013;Su et al, 2013). Hence, RRF may be endowed with potential beneficial effects in relieving perimenopausal symptoms, ameliorating deleterious degeneration in aspects of perimenopausal-associated pituitary-ovarian hormones.…”
Section: Discussionsupporting
confidence: 82%
“…The above dry extracts were blended thoroughly with an appropriate amount of microcrystalline cellulose and crosslinking polyvinylpyrrolidone (PVP) to produce RRF samples for each experiment. HPLC assays as described previously had been employed for assurance of quality control of the typical chemicals of the three herbs, astragaloside IV for RA, ferlic acid for RAS, and icariin for FE (Xie et al, 2013). RRF was stored at 4 °C and diluted to the desired concentrations in distilled 8 water at the time of administration.…”
Section: Plant Materials and Preparation Of Rrfmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we determined the effect of MWM on the serum levels of E 2 , FSH, and LH in a natural aging rat model and showed that MWM increased the circulating levels of E 2 and decreased those of FSH without affecting the levels of LH, similar to the effects of CEE. Similar effects on E 2 /FSH/LH levels were obtained in previous studies using a preparation of herbal medicines designated as RRF, which restored hormonal balance, alleviated reproductive organ and skeleton degeneration, and restored bone mineral density in a rat model [ 18 , 19 ]. On the other hand, Danggui Buxue Tang (DBT), a traditional Chinese preparation used widely to alleviate perimenopausal symptoms, exhibits weak estrogenic properties and its activity was shown to be largely independent of the estrogen receptor in in vivo experiments [ 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…Due to a global population aging, there will be one billion women over the age of 60 years by the year 2050 (Hoga et al, 2015 ). Currently, more than 50% of women in the world are afflicted with postmenopausal syndrome at the climacteric stage (Su et al, 2013 ; Dalal and Agarwal, 2015 ). It is widely accepted that estrogen deprivation plays an important role in the postmenopausal syndrome (World Health Organization, 1996 ; Greendale et al, 1998 ; Constantine and Pickar, 2003 ).…”
Section: Introductionmentioning
confidence: 99%